Correlating Substance Abuse Disorders and Mood Disorder: Clinical Implications of a Dimensional Approach - Chauhan, Shakti; Sharma, Divya Darshani; Siraj, Syed Aaqid; Nagrath, Deepti; Semwal, Jayanti (Indian Journal of Community Health, 2024)
Background: Substance use disorder (SUD) often co-occurs with mood disorders like anxiety and depression. This study investigates the relationship between SUD and mood disorders using a dimensional approach. Methods: A total of 290 participants, including 145 with SUD and 145 healthy controls, were assessed. The General Health Questionnaire (GHQ-12) evaluated mental health, followed by interviews using the Hamilton Anxiety Rating Scale (HAM-A) and Hamilton Depression Rating Scale (HAM-D). Demographic information, substance use behaviours, and mental health symptoms were collected and analysed. Results: Of the participants, 90% were men and 10% women; 68.2% were married. Most SUD patients were smokers (71.0%) and alcohol users (35.8%), with others using drugs or tobacco (33.7% and 19.3%). The majority (84.8%) used drugs for a high. HAM-D results showed moderate to severe depression in 7.5% of SUD patients and 5.5% of controls. HAM-A results indicated 80.6% of the SUD group had anxiety, compared to 88.9% of controls with no anxiety. Conclusion: SUD patients frequently experience concurrent anxiety and depression, highlighting the need for dual diagnosis and integrated treatment for SUD and mood disorders.